A Gender Philosophy for Lima’s Modernity in Two Short Stories by Clorinda Matto de Turner - Grau-Lleveria, Elena (2019)
Combining part of the extensive literature on the literary production of Clorinda Matto de Turner with a feminist ideological framework, this article examines the ideology of gender constructed in relation tomodernity, gender policies and national imaginary in two of his short stories, “Pálida!... pero es ella...! Novela homeopática con pretensiones espiritistas” and “Amor de redondel. Cuento a modo de novela”. This ideology, superficially, presents instabilities and contradictions. However, it is through these apparent contradictions that Matto de Turner could manage her reformist program around gender and national reform without apparently altering the hegemonic rule.